Maintenance of Ciparahu Puncak Lumba Tourism Site Facilities - Selviani, Tasya Bilqis; Fadhilah, Rikza; Sakinatunnisa, Nindhita; Meilawati, Mila; Rasyid, Fahmi; Azis, Dika Dwi Muhammad; Murni, Chintia; Puspitawati, Alin; Agustira, Yuda; Fadzilah, Aldy Rinaldy; Anggraeni, Yunissa; Budi Nugraha, Aditya (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
This study aims to examine the Tourism Village in Ciparahu Hamlet, Dayeuhluhur Village, Kec. Dayeuhluhur, Kab. Cilacap is the Peak of Lumba. This research was conducted using a qualitative descriptive approach to the type of documentation study research. The place of this research is in Puncak Lumba, Ciparahu Hamlet. After we conducted research, the results of this study showed that Puncak Lumba is a tourist spot located on the border between Dayeuhluhur Village and Tambaksari Village.